Fear of recurrence and disease progression in long‐term (≥5 years) cancer survivors—a systematic review of quantitative studies. Issue 1 (10th January 2012) - Koch, L.; Jansen, L.; Brenner, H.; Arndt, V.
Abstract Background Increasing proportions of patients diagnosed with cancer will become long‐term survivors (≥5 years post‐diagnosis). However, survivors may continue to experience negative effects of cancer and/or treatment, including fear of recurrence (FoR). This review aims to provide an overview of current knowledge on FoR, including determinants and consequences in long‐term cancer survivors, and to outline methodological and conceptual challenges that should be addressed in future research. Methods Multiple databases including PUBMED, EMBASE, and PsycINFO were searched to identify relevant articles. Seventeen articles were included. Data were extracted by two reviewers and summarized following a systematic scheme. Results Even years after initial diagnosis, cancer survivors suffer from FoR. Most studies report low or moderate mean FoR scores, suggesting that FoR is experienced in modest intensity by most survivors. Studies including long‐term and short‐term survivors indicate no significant change of FoR over time. Lower level of education, lower level of optimism, and being Hispanic or White/Caucasian were found to be associated with higher levels of FoR. Significant negative associations were reported between FoR and quality of life as well as psychosocial well‐being. All but three studies were conducted in the USA. General cut‐offs for severity/clinical significance have not been defined yet. Conclusions FoR at modest intensity is experienced by most long‐term cancer survivors. Future studies should address determinants and consequences of FoR in more detail. Validated instruments providing cut‐offs for severity/clinical significance of FoR should be developed and utilized. Efficient interventions should be implemented to reduce detrimental effects of FoR. Copyright © 2012 John Wiley & Sons, Ltd.